Takhrij and Syarah Hadith of Agrotechnology: The Role of Olives for Health - Putri Nur Hadiyatus Solehah; Wahyudin Darmalaksana; Efrin Firmansyah (UIN Sunan Gunung Djati Bandung, 2021)
The research aimed to discuss the hadith about olives. This research method is a qualitative type through literature and field studies with the Takhrij and Syarah approaches. The results and discussion of this research is on the role of olives which from the time of the Prophet became a tree rich in benefits ranging from stems, leaves, fruit and oil. The conclusion of this study is the takhrij and syarah of the Prophet about olive trees have fruit, leaves and oil that can be used as anti-infection in internal organs, such as kidneys, bile, and contain colloid compounds that can kill cancer cells.